PENGARUH KUALITAS AUDIT, OPINION SHOPPING, DEBTDEFAULT PERTUMBUHAN PERUSAHAAN DAN KONDISI KEUANGAN PERUSAHAAN TERHADAP PENERIMAAN OPINI AUDITGOING CONCERN - Istiana, Siti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2010)
This research have a purpose to test the effect of Audit Quality, opinion shopping, debt default, company growth and company financial condition to going concern audit opinion acceptance. The sample which used in this research is Manufacture Company which registered in Indonesia Stock Exchange use of 2006-2008. The sample was taken with purposive sampling method and the result 53 companies were match and fulfill the sample criteria. Hypotheses testing was done whit logistic regression test tool from SPSS application program. The research result show that audit quality does not effect to the possibility of going concern audit opinion acceptance, opinion shopping does not effect to the possibility of going concern audit opinion acceptance, debt default have effect to the possibility of going concern audit opinion acceptance, company growth does not effect to the possibility of going concern audit opinion acceptance, and company financial condition have effect to the possibility of going concern audit opinion acceptance.